As at home, so at work? The dynamic of relationship quality, work engagement, and burnout through the lens of basic psychological needs - Lars van Tuin; Maria C.W. Peeters; Willem van Rhenen; Iris Arends; Jurriën den Hollander (PLoS ONE, 2025)
The present study examines the relationship between the quality of partner relationships and work engagement and burnout, considering the satisfaction and frustration of basic psychological needs within that private relationship. We argue that basic psychological needs mediate between the partner relationship and work, serving as an explanatory mechanism in that relationship. We hypothesized that when things go well at home and a person’s basic needs in the partner relationship are fulfilled, it positively associates with work engagement and negatively with burnout. In contrast, we expected that when basic psychological needs are frustrated, it would have a negative relationship with work engagement and a positive relationship with burnout. We analyzed data collected from 317 Dutch residents in committed partner relationships using structural equation modeling in a parallel mediation model. As hypothesized, the results indicate that a supportive partner relationship is associated with higher satisfaction of basic needs, which in turn enhances work engagement and decreases the risk of burnout. Contrary to our hypothesis, we found that the frustration of a partner’s basic psychological needs in the partner relationship was positively associated with increased energy for work (work engagement) and lower levels of exhaustion (burnout). Individuals may channel their energy into work when their partner relationship compromises their basic needs. Implications for practice and future research are discussed.